Osseous Sarcoma: Is Sarcoma the New Emperor of Maladies? Case-Series with Brief Review of the Literature. (2nd May 2019) - Sharma, Dikshya; Narula, Naureen; Mudduluru, Bindu; Joseph, Bino; Elsayegh, Dany
Abstract : Sarcoidosis is multisystem disease that has been amusing physicians since its discovery in 1989 by Caesar Boeck. More than 10, 000 articles have been published in the literature by far, and each time it affects a new organ. Involvement of bone has been recently discovered and because it is still a rare entity, it is important to focus on the presenting systems and also to be able to differentiate it from other closely related diseases including but not limited to tumor and other infectious processes. We describe two cases of osseous sarcoma in two relatively young but surprisingly asymptomatic patients.